Answer:
x = -1 , y = 3
Explanation:
2x+5y = 13
-x+4y = 13
Decide whether to add or subtract the two equations by using Different Add Same Subtract (DASS) or in case below as its SUBTRACT
i apply (SDSS).
We subtract 5y as this is easier equation either positive prioritises or if both positive then easier number becomes priory.
Results to SDSS before substituting Y if 5y etc was subtracted
2x+5y = 13 Subtract -5
2x+5y -5y = 13 -5y
2x= 13 - 5y then Divide by 2
2x / 2 = 13/2 - 5y/2 Show then
x = 13 - 5y / 2 + 4y = 13 Simplify
simplify 13 - 13y / 2 as y = 3
as 13/2 = 6.5 and 2.5 +4 = 6.5
y = 3
Substitute y = 3
13-5y )3) / 2
13-5 (3) / 2
BODMAS Brackets first Multiplying only for y substitute 5y = 5 x 3
-5 (3) = 15
13-15 = -2
-2/2 = -1
x = -1